#TITLE_ALTERNATIVE# - Indri Hapsari Sutarto (NIM:153 03 014), Ratri
Abstract: Many researches showed heavy metals contamination in fish. Heavy metals contamination in fishes can be caused by heavy metals pollution in water, sediment or fish food. This research was conducted to find out the type and concentration of heavy metals content in fish and water. This was done to know if there s any correlation between heavy metals content in water and fish cultured in Cirata water-reservoir. The heavy metal analysis procedure in fish used in this research was based on the extraction method with concentrated nitrate acid (HNO3) according to SNI 06-2464-1991 while for heavy metals analysis in water is based on the extraction method in Standard Methods, 5th Edition, 2001 The heavy metals concentration in fish and water followed a descending order of their concentration, zinc (Zn) > copper (Cu) > plumbum (Pb) > cadmium (Cd) > mercury (Hg). Fish sample were chosen based on weight yield, which is 100-400 grams, and the chosen species is Cyprinus carpio. This weight divided into two groups, which are big fish with weight range of 250-400 grams and small fish with weight range of 100-249 grams. Based on statistic analysis Two-Way ANOVA, it is deducted that there s a correlation between heavy metals content in fish and water, while statistic analysis T-Test Paired sample shows that heavy metal concentration in small fish not always higher than that of big fish. Bio concentration factor (BCF) is applied to the sample to see bio concentration potential from heavy metals. If BCF value of a heavy metal is between 100-1000 and more, the heavy metal have tendency to concentrate in organism body. The magnitude of BCF range in fish for Zn and Cu are above 100 even 1000, showing the tendency to concentrate; while Hg has no tendency to concentrate because it have range below 100. From Acceptable Daily Intake (ADI) calculation known that the value of ADI from Cu, Cd, Pb, and Hg are still below the ADI standard based on FAO/WHO.